Answer:
P + Q = 1
Step-by-step explanation:
Given: [tex]\frac{1+\sqrt{3} }{1-\sqrt{3} }[/tex] = P - [tex]\sqrt{Q}[/tex]
This is a question on surd, so we need to rationalize the denominator to have;
[tex]\frac{1+\sqrt{3} }{1-\sqrt{3} }[/tex] * [tex]\frac{1+\sqrt{3} }{1+\sqrt{3} }[/tex] = [tex]\frac{1+\sqrt{3}+\sqrt{3} + 3}{1+\sqrt{3}-\sqrt{3} -3 }[/tex]
= [tex]\frac{4+ 2\sqrt{3} }{1-3}[/tex]
= [tex]\frac{4+2\sqrt{3} }{-2}[/tex]
= -2 - [tex]\sqrt{3}[/tex]
Thus,
-2 - [tex]\sqrt{3}[/tex] = P - [tex]\sqrt{Q}[/tex]
⇒ P = -2 and Q = 3
Therefore, the value of P + Q = -2 + 3
= 1
Thus,
P + Q = 1